2006
DOI: 10.1071/wf05001
|View full text |Cite
|
Sign up to set email alerts
|

Bromus tectorum cover mapping and fire risk

Abstract: Fire risk in western North America has increased with increasing cover of Bromus tectorum, an invasive alien annual grass. The relationship between B. tectorum cover and fire risk was determined in a historically burned Artemisia tridentata-Poa secunda shrub–steppe community where B. tectorum cover ranged from 5 to 75%. Fire risk ranged from ~46% with an average of 12% B. tectorum cover to 100% when B. tectorum cover was greater than 45% based on prediction confidence limits. Reflectance of the green and red b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 15 publications
1
61
0
Order By: Relevance
“…When wildfires are ignited in dense infestations, the extent and severity of these fires supersedes that of historic fires, thus, negatively impacting the native plant community (Brooks 2002;Link et al 2006). Studies have shown that downy brome recovers to pre-fire levels within two seasons after fire, outcompeting desirable species (Young et al 1976;Melgoza et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…When wildfires are ignited in dense infestations, the extent and severity of these fires supersedes that of historic fires, thus, negatively impacting the native plant community (Brooks 2002;Link et al 2006). Studies have shown that downy brome recovers to pre-fire levels within two seasons after fire, outcompeting desirable species (Young et al 1976;Melgoza et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…These vegeta- continuity, which greatly increases the potential for fi re spread and larger wildfi res (Link et al 2006). …”
Section: Firementioning
confidence: 99%
“…Documentation of plant communities on the disturbance was done on June 14, 2011, by determining cover of each species along with other surface characters. Cover was determined using a tape measure (Bonham 1989;Elmore et al 2003;Link et al 2006) and identifying the first observed (tallest) cover type at each 0.1-m hash mark on the tape. The tape was stretched tightly between two pieces of rebar metal stakes in the ground at the ends of any transect.…”
Section: D25 Cheatgrass Control At High Elevationmentioning
confidence: 99%